2018
DOI: 10.1126/science.aan8690
|View full text |Cite
|
Sign up to set email alerts
|

Different mutational rates and mechanisms in human cells at pregastrulation and neurogenesis

Abstract: Somatic mosaicism in the human brain may alter function of individual neurons. We analyzed genomes of single cells from the forebrains of three human fetuses (15 to 21 weeks postconception) using clonal cell populations. We detected 200 to 400 single-nucleotide variations (SNVs) per cell. SNV patterns resembled those found in cancer cell genomes, indicating a role of background mutagenesis in cancer. SNVs with a frequency of >2% in brain were also present in the spleen, revealing a pregastrulation origin. We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
258
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 239 publications
(297 citation statements)
references
References 42 publications
(54 reference statements)
35
258
4
Order By: Relevance
“…It does face intrinsic limitations, including low throughput, high failure rates of SCNT, low rates of mitotic growth of the newly created cells, incompatibility with humans in requiring the use of laboratory mice, and in some cases a need to generate cloned mice, a process that likely excludes interrogation of cells with highly altered genomes (e.g., aneuploid neurons). Nevertheless, these results demonstrated that individual mitral neurons contain hundreds of unique SNVs, and considering the relatively shorter lifespan of mice vs. humans, the numbers of SNVs in mice are generally consistent with the thousands observed in older human neurons in which SNVs appear to increase with age (Bae et al, ; Lodato et al, ), albeit based upon very few neurons assessed with all of these techniques.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…It does face intrinsic limitations, including low throughput, high failure rates of SCNT, low rates of mitotic growth of the newly created cells, incompatibility with humans in requiring the use of laboratory mice, and in some cases a need to generate cloned mice, a process that likely excludes interrogation of cells with highly altered genomes (e.g., aneuploid neurons). Nevertheless, these results demonstrated that individual mitral neurons contain hundreds of unique SNVs, and considering the relatively shorter lifespan of mice vs. humans, the numbers of SNVs in mice are generally consistent with the thousands observed in older human neurons in which SNVs appear to increase with age (Bae et al, ; Lodato et al, ), albeit based upon very few neurons assessed with all of these techniques.…”
Section: Introductionsupporting
confidence: 71%
“…Also proposed to occur during neurogenesis, mosaic LINE1 insertions, as discussed in a previous section, are theoretically capable of generating GM during the cell cycle (Packer et al, ; Muotri et al, ; Shi et al, ; Singer et al, ; Viollet et al, ; Mita et al, ). By contrast, many neural somatic SNVs have been associated with damage due to transcriptional activity (Lodato et al, ), consistent with increased SNV rates in aged brains (Bae et al, ; Lodato et al, ), suggesting this form of GM is generated in postmitotic neurons. It is entirely possible that other mechanisms could contribute to neural GM, including hypothesized gene recombination, which awaits further investigation.…”
Section: Introductionmentioning
confidence: 75%
“…A very recent study of clonally expanded human foetal forebrain cells has shown 200‐400 SNVs in each. The mutation rate during neurogenesis was estimated at 5.1 per day per progenitor, and was higher than in the first few cell divisions .…”
Section: Note Addedmentioning
confidence: 94%
“…We tested RetroSom in several independent WGS datasets. Data from clonally expanded fetal brain cells 24 confirmed that ≥ 2 supporting reads are necessary for high precision (L1: 99.97%; Alu: 99.99%) with adequate sensitivity (L1: 49.5%; Alu: 82.52%) ( Fig. 2A and Supplementary Note 1).…”
Section: Performance Evaluation On Three Independent Datasetsmentioning
confidence: 71%